Determination of Emission Reduction Costs Through Optimization of Generator Scheduling in Indonesia - Hasudungan, Jaspar; Raharjo, Jangkung (International Journal of Energy Economics and Policy, 2022)
The energy crisis, the impact of emissions, the greenhouse effect, and climate change are global issues. The operation of power plants using fossil fuels impacts emissions that are harmful to the environment. This paper discusses the determination of the cost of reducing plant emissions, which is preceded by solving the problem of scheduling generators involving emissions (often known as Economic Emission Dispatch) for various conditions of variation in cost and emission weights using candidate area reduction techniques. This method was tested using the Java-Bali, Indonesia, 500 kV electrical system, 25 buses, with various loads. The ratio between the cost difference and the emission difference is determined in various conditions from the combination of costs and emissions. The simulation results are compared with other methods such as the firefly algorithm, Cuckoo algorithm, and particle swarm optimization. The results of these various methods show that it costs USD 167.3 to USD 218.1 to reduce emissions by 1 ton per 4 hours. This paper provides input to the government in making policies related to flexible power plant emission control. Considering that emission is a national issue in Indonesia, one of the efforts to reduce emissions from power plants is the implementation of policies related to the operation of plants by considering emissions. However, to avoid counter-productivity from the operation of electricity, the government can prepare funding to assist the electricity operator in implementing the policy for limiting the emission of the power plant.